Deforestation and climate change: acting on the causes What the (carbon) market cannot do... - Karsenty, Alain (Perspective, 2009)
<span style="font-size: 10pt; font-family: Arial; font-style: normal;" data-sheets-value=""1":2,"2":"With an estimated average loss of around 13 million hectares per year between 2000 and 2005 – 7.3 million hectares if reforestation is taken into account, according to FAO –, tropical deforestation is a major source of greenhouse gas emissions. At around 4.4 to 5.5 GtCO2 per year (the latter including peat forest degradation) according to the latest estimates, these emissions account for about 12 to 15% of annual anthropogenic CO2 emissions (from 8 to 20% taking into account the considerable uncertainties in the deforestation and degradation estimates). Moreover, tropical deforestation has a devastating impact on biological diversity, since tropical forests contain over two thirds of the 250 000 higher plants known to scientists. At present, emissions caused by deforestation in developing countries are regulated neither by the Framework Convention on Climate Change nor by the Kyoto Protocol. However, the issue of “avoided deforestation” is expected to be one of the difficult areas of the 15th Conference of the Parties to the UNFCCC (Copenhagen, December 2009), which will propose a post-Kyoto “climate” regime. Is the solution a market mechanism to “reward” actors or a fund to finance reforms that tackle the causes? The debate is open."" data-sheets-userformat=""2":585,"3":[null,0],"6":"1":["1":2,"2":0,"5":[null,2,0],"1":0,"2":0,"3":3,"1":1,"2":0,"4":1],"9":0,"12":0">Version française de l'article <span style="font-size: 10pt; font-family: Arial; font-style: normal;" data-sheets-value=""1":2,"2":"With an estimated average loss of around 13 million hectares per year between 2000 and 2005 – 7.3 million hectares if reforestation is taken into account, according to FAO –, tropical deforestation is a major source of greenhouse gas emissions. At around 4.4 to 5.5 GtCO2 per year (the latter including peat forest degradation) according to the latest estimates, these emissions account for about 12 to 15% of annual anthropogenic CO2 emissions (from 8 to 20% taking into account the considerable uncertainties in the deforestation and degradation estimates). Moreover, tropical deforestation has a devastating impact on biological diversity, since tropical forests contain over two thirds of the 250 000 higher plants known to scientists. At present, emissions caused by deforestation in developing countries are regulated neither by the Framework Convention on Climate Change nor by the Kyoto Protocol. However, the issue of “avoided deforestation” is expected to be one of the difficult areas of the 15th Conference of the Parties to the UNFCCC (Copenhagen, December 2009), which will propose a post-Kyoto “climate” regime. Is the solution a market mechanism to “reward” actors or a fund to finance reforms that tackle the causes? The debate is open."" data-sheets-userformat=""2":585,"3":[null,0],"6":"1":["1":2,"2":0,"5":[null,2,0],"1":0,"2":0,"3":3,"1":1,"2":0,"4":1],"9":0,"12":0">With an estimated average loss of around 13 million hectares per year between 2000 and 2005 – 7.3 million hectares if reforestation is taken into account, according to FAO –, tropical deforestation is a major source of greenhouse gas emissions. At around 4.4 to 5.5 GtCO2 per year (the latter including peat forest degradation) according to the latest estimates, these emissions account for about 12 to 15% of annual anthropogenic CO2 emissions (from 8 to 20% taking into account the considerable uncertainties in the deforestation and degradation estimates). Moreover, tropical deforestation has a devastating impact on biological diversity, since tropical forests contain over two thirds of the 250 000 higher plants known to scientists. At present, emissions caused by deforestation in developing countries are regulated neither by the Framework Convention on Climate Change nor by the Kyoto Protocol. However, the issue of “avoided deforestation” is expected to be one of the difficult areas of the 15th Conference of the Parties to the UNFCCC (Copenhagen, December 2009), which will propose a post-Kyoto “climate” regime. Is the solution a market mechanism to “reward” actors or a fund to finance reforms that tackle the causes? The debate is open.